2007
DOI: 10.1158/1078-0432.ccr-07-0160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an 111In-Radiolabeled Peptide as a Targeting and Imaging Agent for ErbB-2 Receptor–Expressing Breast Carcinomas

Abstract: Purpose: The cellular targeting and tumor imaging properties of a novel ErbB-2-avid peptide, discovered from bacteriophage display, were evaluated in human breast carcinoma cells and in breast carcinoma^xenografted mice. Experimental Design: The affinity of the ErbB-2 targeting peptide KCCYSL and its alanine substituted counterparts for the extracellular domain (ECD) of purified recombinant ErbB-2 (ErbB-2-ECD) was assessed by fluorescence titration. Binding of the KCCYSL peptide to breast and prostate carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 39 publications
5
95
0
4
Order By: Relevance
“…Few other bacteriophage-selected peptides that bind tumor-associated antigens have been reported to function as efficacious tumor imaging agents in vivo. Recently, we successfully used an ErbB-2 receptor-targeting peptide (KCCYSL), derived from a bacteriophage display library, for SPECT/CT of human xenografted breast tumors in mice (18). Here, we demonstrated that 111 In-DOTA(GSG)-G3-C12 can be used to image galectin-3-expressing MDA-MB-435 human breast cancer xenografts in SCID mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few other bacteriophage-selected peptides that bind tumor-associated antigens have been reported to function as efficacious tumor imaging agents in vivo. Recently, we successfully used an ErbB-2 receptor-targeting peptide (KCCYSL), derived from a bacteriophage display library, for SPECT/CT of human xenografted breast tumors in mice (18). Here, we demonstrated that 111 In-DOTA(GSG)-G3-C12 can be used to image galectin-3-expressing MDA-MB-435 human breast cancer xenografts in SCID mice.…”
Section: Discussionmentioning
confidence: 99%
“…The 111 In-labeling of DOTA(GSG)-ANTPCGPYTHDCPVKR (G3-C12) or DOTA(GSG)-PPPKGDVHTNRTYACC (scrambled version of G3-C12) was performed essentially as previously described (18). Briefly, the peptides were radiolabeled with 111 In by incubating 25 mg of peptide in 5 mL of 111 InCl 3 (185 MBq/500 mL) (Mallinckrodt) and 80 mL of ammonium acetate, pH 5.5, at 85°C for 60 min, after which 10 mL of 2 mM ethylenediamine tetraacetic acid were added to complex unreacted 111 In.…”
Section: Peptide Radiolabelingmentioning
confidence: 99%
“…After production by solid phase synthesis, electrospray ionization mass spectrometry analysis found that the peptide exists as a mixture of oxidized and reduced monomer in solution without measurable amounts of a dimeric form. The binding affinity to recombinant ErbB2-ECD, as determined by fluorescence titration experiments in solution, was reported to be K D ~300 nM (Kumar et al 2007). A DOTA chelating group was added to the N-terminus of the peptide through a Gly-Ser-Gly linker and labeled with 111 In.…”
Section: Molecular Imaging Agents Obtained Using Purified Targetsmentioning
confidence: 99%
“…A molecular imaging approach using certain fluorescent probes may vastly improve signal-to-noise ratios by signal amplification [27]. Target-specific fluorescent probes for optical imaging have already been used successfully in animal experiments [28][29][30].…”
Section: Discussionmentioning
confidence: 99%